2018
DOI: 10.1088/1674-4527/18/11/141
|View full text |Cite
|
Sign up to set email alerts
|

Log-normal flux distribution of bright Fermi blazars

Abstract: We present the results of the γ-ray flux distribution study on the brightest blazars which are observed by the Fermi-LAT. We selected 50 brightest blazars based on the maximum number of detection reported in the LAT third AGN catalog. We performed standard unbinned maximum likelihood analysis on the LAT data during the period between August 2008 and December 2016, in order to obtain the average monthly flux. After quality cuts, blazars for which at least 90% of the total flux was survived were selected for the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 30 publications
2
63
0
Order By: Relevance
“…Thanks to its constant monitoring, a great deal of data is available to study the statistical properties of AGN light curves. Studies on the brightest blazars seen by the LAT show the same trend when the light curves are binned on a monthly timescale [11]. However, the Fermi-LAT, having a collection area of ∼1 m 2 , lacks the necessary sensitivity to perform a detailed study also on fainter objects, where it can become hard to gain enough statistics on short timescales to perform these kind of studies, as shown in Section 2.…”
Section: Observational Evidences In Gamma Raysmentioning
confidence: 75%
“…Thanks to its constant monitoring, a great deal of data is available to study the statistical properties of AGN light curves. Studies on the brightest blazars seen by the LAT show the same trend when the light curves are binned on a monthly timescale [11]. However, the Fermi-LAT, having a collection area of ∼1 m 2 , lacks the necessary sensitivity to perform a detailed study also on fainter objects, where it can become hard to gain enough statistics on short timescales to perform these kind of studies, as shown in Section 2.…”
Section: Observational Evidences In Gamma Raysmentioning
confidence: 75%
“…The almost continuous detection of the investigated sources over time bins of seven days provides a good opportunity to investigate whether the probability density function (PDF) for the long-term γ-ray emission reveals any preference for a gaussian (normal) or a log-normal flux distribution. It is expected that such a feature offers an important clue for understanding the central engine of a blazer (e.g., Uttley et al 2005;Shah et al 2018). A log-normal distribution of γ-ray fluxes, for example, would suggest that the mechanism driving the variability is multiplicative in nature rather than additive.…”
Section: Gaussian Vs Log-normal Flux Distributionsmentioning
confidence: 99%
“…A log-normal distribution of γ-ray fluxes, for example, would suggest that the mechanism driving the variability is multiplicative in nature rather than additive. Such multiplicative behaviour might possibly be related to accretion disk fluctuations (Lyubarskii 1997;Arévalo & Uttley 2006) or the particle acceleration process itself (Shah et al 2018). As a possible caveat we note that PDF of stochastic processes with power spectral density (PSD) steeper than index −1 can show deviations from normality owing to divergence of power at low frequencies (e.g., Vaughan et al 2003).…”
Section: Gaussian Vs Log-normal Flux Distributionsmentioning
confidence: 99%
“…While the flux distribution of blazars follows a normal distributions at GeV energies, the fluxes measured by current IACTs have a clear preference for log-normal distributions, suggesting multiplicative rather than additive processes at their origin [109][110][111]. However, the observations of most IACTs are biased, as the observations are usually not carried out in a monitoring mode but often based on triggers by other instruments.…”
Section: Blazar Variabilitymentioning
confidence: 99%